Disseminated cutaneous herpes zoster in an immunocompetent elderly patient - Eric Gomez; Ivan Chernev (MDPI AG, 2014)
Herpes zoster is a clinical syndrome which usually presents with a localized, vesicular rash in a dermatomal distribution. Cutaneous dissemination rarely occurs in immunocompetent patients, therefore little is known about the baseline demographic, clinical characteristics, management and outcome of these patients. Herein, we report a case of disseminated cutaneous herpes zoster in an immunocompetent patient along with a review and analysis of 28 cases previously reported in the literature.